The Use of Carbon Dioxide (CO2) as a Building Block in Organic Synthesis from an Industrial Perspective. Issue 2 (27th November 2018) - Dabral, Saumya; Schaub, Thomas
Abstract: The use of carbon dioxide (CO2 ) as a building block in organic synthesis is a topic of high interest. We here reflect from an industrial perspective, which of the approaches may have the potential to be applied in the near future in industrial organic synthesis on a significant scale. Drawbacks to overcome and challenges to be addressed are also discussed in this critical review. This review focuses on systems providing a high atom‐efficiency and which could be competitive to other state‐of‐the art syntheses. Abstract :